47.9k views
11 votes
For the following pair of functions, find (f+g)(x) and (f-g)(x).

f(x)= 4x2 + 7x-5 and g(x)= - 9x² + 4x - 13
(f+g)(x) = 0
(Simplify your answer. Type in descending order.)
(f-g)(x) =
(Simplify your answer. Type in descending order.)

1 Answer

12 votes

Given:

The functions are


f(x)=4x^2+7x-5


g(x)=-9x^2+4x-13

To find:

The functions
(f+g)(x) and
(f-g)(x).

Solution:

We know that,


(f+g)(x)=f(x)+g(x)


(f+g)(x)=4x^2+7x-5-9x^2+4x-13


(f+g)(x)=(4x^2-9x^2)+(7x+4x)+(-5-13)


(f+g)(x)=-5x^2+11x-18

And,


(f-g)(x)=f(x)-g(x)


(f-g)(x)=(4x^2+7x-5)-(-9x^2+4x-13)


(f+g)(x)=4x^2+7x-5+9x^2-4x+13


(f+g)(x)=(4x^2+9x^2)+(7x-4x)+(-5+13)


(f-g)(x)=13x^2+3x+8

Therefore, the required functions are
(f+g)(x)=-5x^2+11x-18

and
(f-g)(x)=13x^2+3x+8.

User Aren
by
5.9k points